Aspirin enhances protective effect of fish oil against thrombosis and injury‐induced vascular remodelling. (12th January 2015) - Gong, Yanjun; Lin, Minghui; Piao, Lingjuan; Li, Xinzhi; Yang, Fei; Zhang, Jian; Xiao, Bing; Zhang, Qingli; Song, Wen‐Liang; Yin, Huiyong; Zhu, Li; Funk, Colin D; et al.
Abstract : Background and Purpose: Although aspirin (acetylsalicylic acid) is commonly used to prevent ischaemic events in patients with coronary artery disease, many patients fail to respond to aspirin treatment. Dietary fish oil (FO), containing ω3 polyunsaturated fatty acids (PUFAs), has anti‐inflammatory and cardio‐protective properties, such as lowering cholesterol and modulating platelet activity. The objective of the present study was to investigate the potential additional effects of aspirin and FO on platelet activity and vascular response to injury. Experimental Approach: Femoral arterial remodelling was induced by wire injury in mice. Platelet aggregation, and photochemical‐ and ferric chloride‐induced carotid artery thrombosis were employed to evaluate platelet function. Key Results: FO treatment increased membrane ω3 PUFA incorporation, lowered plasma triglyceride and cholesterol levels, and reduced systolic BP in mice. FO or aspirin alone inhibited platelet aggregation; however, when combined, they exhibited synergistic suppression of platelet activity in mice, independent of COX‐1 inhibition. FO alone, but not aspirin, attenuated arterial neointimal growth in response to injury. Strikingly, a combination of FO and aspirin synergistically inhibited injury‐induced neointimal hyperplasia and reduced perivascular inflammatory reactions. Moreover, co‐administration of FO and aspirin decreased the expression of pro‐inflammatory cytokines and adhesion molecules in inflammatory cells. Consistently, a pro‐resolution lipid mediator‐Resolvin E1, was significantly elevated in plasma in FO/aspirin‐treated mice. Conclusions and Implications: Co‐administration of FO and low‐dose aspirin may act synergistically to protect against thrombosis and injury‐induced vascular remodelling in mice. Our results support further investigation of adjuvant FO supplementation for patients with stable coronary artery disease. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23